Topology-based optimization of maximal sustainable throughput in a latency-insensitive system - Collins, Rebecca L.; Carloni, Luca P. (2007 44th ACM/IEEE Design Automation Conference, 2007)
We consider the problem of optimizing the performance of a latency-insensitive system (LIS) where the addition of backpressure has caused throughput degradation. Previous works have addressed the problem of LIS performance in different ways. In particular, the insertion of relay stations and the sizing of the input queues in the shells are the two main optimization techniques that have been proposed. We provide a unifying framework for this problem by outlining which approaches work for different system topologies, and highlighting counterexamples where some solutions do not work. We also observe that in the most difficult class of topologies, instances with the greatest throughput degradation are typically very amenable to simplifications. The contributions of this paper include a characterization of topologies that maintain optimal throughput with fixed-size queues and a heuristic for sizing queues that produces solutions close to optimal in a fraction of the time.